Systems biology reveals key tissue-specific metabolic and transcriptional signatures involved in the response of Medicago truncatula plant genotypes to salt stress - Filippou, Panagiota S.; Zarza, Xavier; Antoniou, Chrystalla; Obata, Toshihiro; Villarroel, Carlos A.; Ganopoulos, Ioannis; Harokopos, Vaggelis; Gohari, Gholamreza; Aidinis, Vassilis; Madesis, Panagiotis; Christou, Anastasis; Fernie, Alisdair R.; et al. (My University, 2021)
Salt stress is an important factor limiting plant productivity by affecting plant physiology and metabolism. To explore salt tolerance adaptive mechanisms in the model legume Medicago truncatula, we used three genotypes with differential salt-sensitivity: TN6.18 (highly sensitive), Jemalong A17 (moderately sensitive), and TN1.11 (tolerant). Cellular damage was monitored in roots and leaves 48 h after 200 mM NaCl treatment by measuring lipid peroxidation, nitric oxide, and hydrogen peroxide contents, further supported by leaf stomatal conductance and chlorophyll readings. The salt-tolerant genotype TN1.11 displayed the lowest level of oxidative damage, in contrast to the salt sensitive TN6.18, which showed the highest responses. Metabolite profiling was employed to explore the differential genotype-related responses to stress at the molecular level. The metabolic data in the salt tolerant TN1.11 roots revealed an accumulation of metabolites related to the raffinose pathway. To further investigate the sensitivity to salinity, global transcriptomic profiling using microarray analysis was carried out on the salt-stressed sensitive genotypes. In TN6.18, the transcriptomic analysis identified a lower expression of many genes related to stress signalling, not previously linked to salinity, and corresponding to the TIR-NBS-LRR gene class. Overall, this global approach contributes to gaining significant new insights into the complexity of stress adaptive mechanisms and to the identification of potential targets for crop improvement.
Keywords: Metabolomics; Raffinose pathway; Salinity; Transcriptomics